The Influence Of Profitability, Capital Intensity, Independent Board Of Commissioners, Audit Committee, Managerial Ownership And nstitutional Ownership On Tax Avoidance: Study of Secondary Consumer Goods Industry Companies Listed on the Indonesian Stock Exchange 2016-2020 - Asri Krisnawati; Sarsiti Sarsiti; Alyssa Mellindina (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The objective of this research is to examine the impact of profitability, capital intensity, independent board of commissioners, audit committee, managerial ownership and institutional ownership on tax avoidance in secondary consumer goods industry companies listed on the Indonesia Stock Exchange in 2016-2020. The sample was selected using purposive sampling method. The total sample used amounted to 34 secondary consumer goods industrial companies 5 years of observation. The analysis technique used is multiple regression analysis. Indication of the reasrch conclude that capital intensity has a positive impact, managerial ownership negatively affect, institutional ownership has a negative impact on tax avoidance. Meanwhile profitability, independent board’s commissioners and audit committee have no impact on tax avoidance.